Geomonas oryzae gen. nov., sp. nov., Geomonas edaphica sp. nov., Geomonas ferrireducens sp. nov., Geomonas terrae sp. nov., Four Ferric-Reducing Bacteria Isolated From Paddy Soil, and Reclassification of Three Species of the Genus Geobacter as Members of the Genus Geomonas gen. nov. - Xu, Zhenxing; Masuda, Yoko; Itoh, Hideomi; Ushijima, Natsumi; Shiratori, Yutaka; Senoo, Keishi (Frontiers in Microbiology, 2019)
In paddy soil, bacteria from the family Geobacteraceae have been shown to strongly contribute to the biogeochemical cycle. However, no Geobacteraceae species with validly published names have been isolated from paddy soil. In this study, we isolated and characterised four novel ferric reducing bacteria in the family Geobacteraceae from the paddy soils of three different fields in Japan. The four strains, S43T, Red53T, S62T, and Red111T, were Gram-stain negative, strictly anaerobic, chemoheterotrophic, and motile with peritrichous flagella. Phylogenetic studies based on 16S rRNA gene sequences, five concatenated housekeeping genes (fusA, rpoB, recA, nifD, and gyrB) and 92 concatenated core genes revealed that the four strains belong to the family Geobacteraceae and are most closely related to Geobacter bemidjiensis BemT (97.4–98.2%, 16S rRNA gene sequence similarities) and Geobacter bremensis Dfr1T (97.1–98.0%). Genomic analysis with average nucleotide identity (ANI) and digital DNA–DNA hybridization (GGDC) calculations clearly distinguished the four isolated strains from other species of the family Geobacteraceae and indicated that strains S43T, Red53T, S62T, and Red111T represent independent species, with values below the thresholds for species delineation. Chemotaxonomic characteristics, including major fatty acid and whole cell protein profiles, showed differences among the isolates and their closest relatives, which were consistent with the results of DNA fingerprints and physiological characterisation. Additionally, each of the four isolates shared a low 16S rRNA gene sequence similarity (92.4%) and average amino acid identity (AAI) with the type strain of the type species Geobacter metallireducens. Overall, strains S43T, Red53T, S62T, and Red111T represent four novel species, which we propose to classify in a novel genus of the family Geobacteraceae, and the names Geomonas oryzae gen. nov., sp. nov. (type strain S43T), Geomonas edaphica sp. nov. (type strain Red53T), Geomonas ferrireducens sp. nov. (type strain S62T), and Geomonas terrae sp. nov. (type strain Red111T) are proposed. Based on phylogenetic and genomic analyses, we also propose the reclassification of Geobacter bremensis as Geomonas bremensis comb. nov., Geobacter pelophilus as Geomonas pelophila comb. nov., and Geobacter bemidjiensis as Geomonas bemidjiensis comb. nov.